Assessing Applause Density Perception Using Synthesized Layered Applause Signals - Adami, Alexander; Disch, Sascha; Steba, Garri; Herre, Jürgen (Proceedings of the International Conference on Digital Audio Effects, DAFx, 2016)
Applause signals are the sound of many persons gathered in one place clapping their hands and are a prominent part of live music recordings. Usually, applause signals are recorded together or alongside with the live performance and serve to evoke the feeling of participation in a real event within the playback recipient. Applause signals can be very different in character, depending on the audience size, location, event type, and many other factors. To characterize different types of applause signals, the attribute of 'density' appears to be suitable. This paper reports first investigations whether density is an adequate perceptual attribute to describe different types of applause. We describe the design of a listening test assessing density and the synthesis of suitable, strictly controlled stimuli for the test. Finally, we provide results, both on strictly controlled and on naturally recorded stimuli, that confirm the suitability of the attribute density to describe important aspects of the perception of different applause signal characteristics.
herre_papers_applause